Prevention of Hospital-Acquired Adverse Drug Reactions in Older People Using Screening Tool of Older Persons' Prescriptions and Screening Tool to Alert to Right Treatment Criteria: A Cluster Randomized Controlled Trial - O'Connor, Marie N.; O'Sullivan, David; Gallagher, Paul F.; Eustace, Joseph; Byrne, Stephen; O'Mahony, Denis (Journal of the American Geriatrics Society (JAGS), 2016)
Objectives To determine whether use of the Screening Tool of Older Persons' Prescriptions (STOPP) and Screening Tool to Alert to Right Treatment (START) criteria reduces incident hospital‐acquired adverse drug reactions (ADRs), 28‐day medication costs, and median length of hospital stay in older adults admitted with acute illness. Design Single‐blind cluster randomized controlled trial (RCT) of unselected older adults hospitalized over a 13‐month period. Setting Tertiary referral hospital in southern Ireland. Participants Consecutively admitted individuals aged 65 and older (N = 732). Intervention Single time point presentation to attending physicians of potentially inappropriate medications according to the STOPP/START criteria. Measurements The primary outcome was the proportion of participants experiencing one or more ADRs during the index hospitalization. Secondary outcomes were median length of stay (LOS) and 28‐day total medication cost. Results One or more ADRs occurred in 78 of the 372 control participants (21.0%; median age 78, interquartile range (IQR) 72–84) and in 42 of the 360 intervention participants (11.7%; median age 80, IQR 73–85) (absolute risk reduction = 9.3%, number needed to treat = 11). The median LOS in the hospital was 8 days (IQR 4–14 days) in both groups. At discharge, median medication cost was significantly lower in the intervention group (€73.16, IQR €38.68–121.72) than in the control group (€90.62, IQR €49.38–162.53) (Wilcoxon rank test Z statistic = −3.274, P < .001). Conclusion Application of STOPP/START criteria resulted in significant reductions in ADR incidence and medication costs in acutely ill older adults but did not affect median LOS.